The Effectiveness of Environmental Law within Regional Development Policies in Disaster-Prone Areas of Sumatra - Febrian Chandra; Harmaini; Rizki Apriadi Bahri; Habibi; Muhammad Reza Halomoan; Rabbiq Qalbi (Adagium: Jurnal Ilmiah Hukum, 2026)
This study aims to analyze the effectiveness of environmental law within the framework of regional development policies in Sumatra Island, specifically in mitigating ecological disaster risks. Sumatra faces a dual challenge of accelerated infrastructure development and high vulnerability to disasters. The research method employed is juridical-normative with a statutory and case study approach, supported by a systematic literature review of secondary data regarding spatial planning and disaster mitigation policies. The results indicate that although legal instruments such as Environmental Impact Assessment (AMDAL) and Strategic Environmental Assessment (KLHS) are regulated, their implementation is often neglected for short-term investment interests, especially after the enactment of the Job Creation Law. There is a significant gap between national green-oriented planning and the reality of regional planning (RTRW/RPJMD) in Sumatra, where planning documents have not fully adopted low-carbon development principles. The impact of this research recommends the need for harmonization of central and regional regulations and strengthening of administrative law enforcement based on political ecology to ensure sustainable and disaster-resilient development.